Feminist poetics : poiesis, performance, histories - Threadgold, Terry (Routledge, 1997)
Feminist Poetics in concerned with all of these questions, but also with the issue of rewriting an older poetics for what it does not say about the marginalisation of the feminine. The first half of the book traces the trajectory of a particular, feminine, academic subject learning to find her voice. The second half uses that differently disciplined voice to re-read the textual traces of the Governor murder stories, murders committed against white women and children by black men in Australia in 1900. This book is a feminist poetics for those who are engaged in the teaching of literaci.